Exploring Cognitive Processes of Knowledge Acquisition to Upgrade Academic Practices - Cherukunnath, Deepa; Singh, Anita Puri (Frontiers in Psychology, 2022)
The development of cognitive functions follows certain pathways through brain maturation. Concepts taught at school can be reinforced by understanding the related cognitive functions that enhance learning. The cultural and social diversities faced by the education system worldwide can be solved by understanding the unifying cognitive processes of learning. This knowledge can be effectively used to devise better curriculum and training of students. Cognition, conation, and emotional regulation are the main components that determine an individual’s efficiency to deal with various situations. How the brain receives input, perceives, and organizes these information lays the foundation for learning. The objectives of the study were (i) to explore age-group specific inputs for knowledge acquisition, (ii) to relate knowledge organization to the cognitive processes, and, (iii) identify factors that strengthens the knowledge ensemble through subject-domain allied training. The review focussed on studies related to elementary school age (below 7 years), middle school age (7 to 12 years), and, high school age (12 years and above). Published journal articles related to the objectives were randomly reviewed to establish a possible relationship. The findings of this review can help to advance student learning practices and instructional strategies. i) Acquisition of knowledge during early childhood is based on sensorimotor integration on which attentional, perceptual, memory, language, and socialization systems develops. As the brain development progresses towards adolescence, meta- awareness and social-emotional cognition influences the student learning process. ii) Knowledge representations can be strengthened by domain specific training inputs iii) Associational integration of the developmental, cognitive and conative processes are indicators of curriculum strength iv) The strengthening of cognitive processes by rerouting through complementary neural circuitry such as music, arts, real life-based experiments and physical exercises are effective ways for improving child-friendly instructions.